2022
DOI: 10.29207/resti.v6i2.3849
|View full text |Cite
|
Sign up to set email alerts
|

Live Forensic to Identify the Digital Evidence on the Desktop-based WhatsApp

Abstract: The live forensics method was used to acquire lawful digital evidence data from device memory in the WhatsApp application, particularly for desktop-based WhatsApp. There has been little research on live forensics on desktop-based WhatsApp applications. These studies involve mimicking crime cases in cyberspace using the Instant Messenger application. Much of the acquisition process is completed only once, even though many possible conditions may arise during the purchase process. Investigators or experts can em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…The Infinix Inbook x1 laptop was deployed as research tool while Microsoft Excel displays visualizations in analyzing the performance of services used on the Adhoc network. Each research objective was addressed using algorithm in the form of flowchart [13] which is shown in the figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…The Infinix Inbook x1 laptop was deployed as research tool while Microsoft Excel displays visualizations in analyzing the performance of services used on the Adhoc network. Each research objective was addressed using algorithm in the form of flowchart [13] which is shown in the figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…In the examined case, the user of EAS key is able to help the investigator in obtaining the result of acquisition although not all of the ransomware family can apply the similar technique. 5 [20] Live forensic Live Forensic techniques are precise to be used to acquire volatile data characteristics. In certain cases, live forensic technique is limited for processing the data obtained from memory.…”
Section: Forensic Techniquesmentioning
confidence: 99%
“…This comparative study is considered to be able to help the investigators in revealing the running cases. Live forensic technique is specifically used by [20] to identify digital evidence in desktopbased WhatsApp.…”
Section: Introductionmentioning
confidence: 99%
“…The ADAM approach was selected since it was created from a number of earlier methods that were based on earlier investigations." It is suggested to utilize the ADAM method while performing a series of investigations utilizing "digital evidence up to the reporting stage of the investigation's conclusions since the phases are more thorough than those of other approaches" [1], [10], [11].…”
Section: Introductionmentioning
confidence: 99%